Clinical and Laboratory Characteristics of COVID-19 Patients Admitted in A Tertiary Hospital of Nepal - Yadav, Naval Kishor; Sah, Rajan Kumar; Singh, Navneet (Journal of College of Medical Sciences-Nepal, 2024)
Background COVID-19 disease is a respiratory infection. The symptoms range from mild fever and bodyache to multiple organ dysfunction. It was first seen in Wuhan, China and later infected whole world in a very short period of time. The aim of this study was to find the clinical and laboratory Characteristics of COVID-19 patients admitted in tertiary hospital of Nepal. Methods This was a cross-sectional hospital based study conducted at Manipal Teaching Hospital, Pokhara, Nepal. The patients with confirmed COVID-19 were included in this study. Questionnaire was used to collect the clinical data and venous blood samples were collected for laboratory parameters. The numerical data were presented in Mean and SD while categorical data were in frequency and percentage. Results The Major infected patient were male (67.9%). The major symptoms observed were shortness of breath (78.8%), dry cough (54.5%), chill (60.3%), wet cough (16.7%) and headache (25%). 60.9% COVID-19 patients were in moderate stage followed by severe stage (26.3%). The complication noticed were cardiac, bacterial infection, ARDS, septic shock and GI bleeding. The level of blood urea, creatinine, AST, ALT, serum ferritin and CRP were found high in COVID-19 patients. Similarly, the level of sodium, potassium, d-dimer, total protein, albumin, WBC and platelets were found within normal limits. Conclusions The common symptoms in COVID-19 patients were shortness of breath, dry cough, chill and headache. The blood level of AST, ALT, ferritin, CRP, urea and creatinine were high in COVID-19 patients.